2014
DOI: 10.3892/ijo.2014.2762
|View full text |Cite
|
Sign up to set email alerts
|

B-cell translocation gene 1 serves as a novel prognostic indicator of hepatocellular carcinoma

Abstract: Although the B‑cell translocation gene 1 (BTG1) plays an important role in apoptosis and negatively regulates cell proliferation, BTG1 expression in hepatocellular carcinoma (HCC) has not been evaluated. In this study expression analysis of BTG1 was conducted to clarify the role of BTG1 in the initiation of HCC carcinogenesis and progression. BTG1 mRNA expression levels were determined for HCC cell lines and 151 surgical specimen pairs using quantitative real‑time reverse transcription polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…The HCC cell lines (Hep3B, HepG2, HLE, HLF, HuH1, HuH2, HuH7, PLC/PRF/5 and SK-Hep1) were obtained from the American Type Culture Collection (Manassas, VA, USA). All cell lines were cultured in Dulbecco's modified Eagle's Medium (Sigma-Aldrich, St. Louis, MO, USA), supplemented with 10% fetal bovine serum at 37˚C in an atmosphere containing 5% CO 2 (6). The primary HCC tissues and the corresponding non-cancerous tissues were collected from 151 patients with HCC who had undergone liver resection at the Nagoya University Hospital (Nagoya, Japan) between January 1998 and July 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HCC cell lines (Hep3B, HepG2, HLE, HLF, HuH1, HuH2, HuH7, PLC/PRF/5 and SK-Hep1) were obtained from the American Type Culture Collection (Manassas, VA, USA). All cell lines were cultured in Dulbecco's modified Eagle's Medium (Sigma-Aldrich, St. Louis, MO, USA), supplemented with 10% fetal bovine serum at 37˚C in an atmosphere containing 5% CO 2 (6). The primary HCC tissues and the corresponding non-cancerous tissues were collected from 151 patients with HCC who had undergone liver resection at the Nagoya University Hospital (Nagoya, Japan) between January 1998 and July 2012.…”
Section: Methodsmentioning
confidence: 99%
“…An important strategy to improve patient outcome involves the identification of disease risk factors and the maintenance of vigilant surveillance of high-risk individuals to allow for recognition of the disease at a stage that is responsive to treatment with curative intent. Therefore, it is fundamental that high-risk groups are identified, followed by successful implementation of a surveillance program and recall protocol following any abnormal findings (5)(6)(7)(8). Progress has been made in identifying molecular markers for the initiation and progression of HCC that will likely increase the rate of early and potentially life-saving diagnoses (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding noncancerous liver tissue samples lacking regenerative or dysplastic nodules were collected [2 cm from the edge of the tumor from the same patient. 19,20 Postoperative follow-up included physical examinations, measurement of serum tumor markers every 3 months, and enhanced computed tomography every 6 months. Treatment after recurrence included surgery, radiofrequency ablation, transcatheter arterial chemoembolization, and chemotherapy, according to tumor status and liver function.…”
Section: Sample Collectionmentioning
confidence: 99%
“…KAL1 protein localization was determined by IHC using 64 representative formalin-fixed and paraffin-embedded sections of wellpreserved HCC tissue using a rabbit polyclonal antibody against KAL1 (ABN486, Millipore, Darmstadt, germany) diluted 1:150 in antibody diluent (Dako, glostrup, Denmark) as previously described (7,31). samples were then washed with phosphate-buffered saline, followed by 10 min incubation with a biotinylated secondary antibody (Histofine sAB-PO(R), Nichirei, Tokyo, japan).…”
Section: Expression Of Genes That Encode Cell Adhesion Factorsmentioning
confidence: 99%
“…Aberrant DNA methylation is one of the most common epigenetic alterations in malignancies and is specific to individual organs and diseases (6)(7)(8). Furthermore, several studies have shown that aberrant DNA methylation contributes to the initiation and progression of malignant tumors through inactivation of tumor suppressors (9,10).…”
Section: Introductionmentioning
confidence: 99%